2020
DOI: 10.1053/j.ackd.2020.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Medical Education During the Coronavirus Disease-2019 Pandemic: Learning From a Distance

Abstract: As paradigms of clinical care delivery have been significantly impacted by the novel coronavirus disease-2019 pandemic, so has the structure, delivery, and future of medical education. Both undergraduate and graduate medical education have seen disruptions ranging from fully virtual delivery of educational content and limited clinical care for medical students to increased clinical demands with redeployment for residents and fellows. Adherence to social distancing has led to the adoption and implementation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
244
0
22

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(273 citation statements)
references
References 22 publications
7
244
0
22
Order By: Relevance
“…Our resort to this means of content delivery is not new, 36 and follows other medical specialties that adapted rapidly to the limitations brought on by the pandemic. 37 However, to the best of our knowledge, this is the first study to systematically assess the delivery of emotionally charged and personal content through this format, an initiative that can be construed under the label of virtual wellness . Indeed, we found that collaboratively engaging in candid conversations about sensitive topics in this setting was not only feasible, but may have had unique advantages: (1) No back row : every student was faced-forward and given a level playing field, with no eager students up front while others hid in the back; (2) A portal to the personal : students and instructors were framed in the revealing setting of their natural home environment, creating a unique opportunity to get to know each other in a more intimate way, one that was conducive to openness (in the words of a participant, “it did make a big difference, even something as small as when the doctor picked up the laptop and walked over to show us a really messy home office.…”
Section: Discussionmentioning
confidence: 99%
“…Our resort to this means of content delivery is not new, 36 and follows other medical specialties that adapted rapidly to the limitations brought on by the pandemic. 37 However, to the best of our knowledge, this is the first study to systematically assess the delivery of emotionally charged and personal content through this format, an initiative that can be construed under the label of virtual wellness . Indeed, we found that collaboratively engaging in candid conversations about sensitive topics in this setting was not only feasible, but may have had unique advantages: (1) No back row : every student was faced-forward and given a level playing field, with no eager students up front while others hid in the back; (2) A portal to the personal : students and instructors were framed in the revealing setting of their natural home environment, creating a unique opportunity to get to know each other in a more intimate way, one that was conducive to openness (in the words of a participant, “it did make a big difference, even something as small as when the doctor picked up the laptop and walked over to show us a really messy home office.…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, no sector was not influenced by COVID-19 crisis yet with different degrees. Such as the examination of COVID-19 pandemic impacts on a medical education sector by (Hilburg et al, 2020). This is going in the same direction as what was provided by Mehta & Wang (2020), they indicated that services associated with education had a share of change in the COVID-19 periods.…”
Section: -Research Conclusion and Discussionmentioning
confidence: 68%
“…The universities' interest in keeping their websites updated during the crisis time was observed. This crisis affected the education system, as explained by (Hilburg et al, 2020), also in this period, distance education had an impact on students and teachers (Kennedy & Ferdig, 2018), No doubt that being responsive and developing well-structured managing and mitigating plans are essential. This is aligned with the fact of most universities developed plans to deal with emergencies as mentioned by (Izumi, 2020).…”
Section: -Research Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations